A helyzet-és személyspecifikus problémamegoldás kapcsolata a tudatelméleti működéssel 4-6 éves korban - Gál, Zita; Kasik, László (Magyar Pedagógia, 2015)
Our study focuses on the relationship between theory of mind (ToM, measured with first-order and second-order false belief tests) and social problem solving (SPS, measured with a self-developed test) among kindergarten children (4–6 years of age, N=145). The SPS test contains eight situations focusing on interpersonal problems. The situations are evaluated along the following dimensions: positive and negative orientation, self-efficacy, rationality, impulsivity and avoidance. Accordingto our results, there are age-related differences in ToM measured with first-and second-order false belief tasks. With regard to SPS, negative self-efficacy was more frequently mentioned among the older children (“I can’t solve the problem”) than among the younger age groups. We found that positive emotions were more often noted among 5-and 6-year-olds, and 4-year-olds asked for help to solve a problem more often than the older age groups. We found relationships between ToM and SPS: there is a positive relationship between positive emotion expression and ToM, while a negative relationship was found between ToM and asking for help from peers and adults. The children who successfully performed a first-order ToM task were characterized by higher positive emotion expression and lower negative emotion expression. We also found that the children who successfully performed a second-order ToM task were characterized by higher positive emotion expression, but they did not ask for help from a peer or teacher in problem solving.